History of Yellow River and Yangtze River delivering sediment to the Yellow Sea since 3.5 Ma: Tectonic or climate forcing?. (15th July 2019) - Zhang, Jin; Wan, Shiming; Clift, Peter D.; Huang, Jie; Yu, Zhaojie; Zhang, Kaidi; Mei, Xi; Liu, Jian; Han, Zhiyong; Nan, Qingyun; Zhao, Debo; Li, Anchun; et al.
Abstract: Reconstructing the Plio-Pleistocene sedimentary history of the Yellow Sea, is important for understanding the long-term influence of the Yellow River (Huanghe) and/or Yangtze River (Changjiang) on the Asian marginal seas and to further constrain any links between river development, regional paleoenvironmental change, tectonic deformation and/or global climate change. Here we present the first high-resolution clay mineral record combined with Sr-Nd isotopic compositions from a 300-m long sediment core recovered in the western South Yellow Sea. Our study suggests that large-scale transgression in the Yellow Sea occurred after ∼0.8 Ma, possibly related to tectonic subsidence of eastern China coast and the Min-Zhe Uplift. In contrast, the sedimentary environment of Bohai and Yellow Seas was mainly dominated by fluvial/lacustrine deposits at 3.5–0.8 Ma. Provenance analysis suggests a major change in sediment provenance from the Yangtze River to the Yellow River at ∼0.8 Ma, which corresponds to the timing of the final integration of the Yellow River in its present form. At the same time the major channels of the Yangtze River migrated from the South Yellow Sea to the modern Yangtze River delta due to the subsidence of east China coast. The consistence in timing of the provenance transition and large-scale regional marine transgression suggests that tectonic deformation, rather than climate change, is the first-order control on the evolution of the Yellow and Yangtze Rivers and sedimentary environmental change in the Bohai and Yellow Seas. Highlights: A major change in sediment provenance in South Yellow Sea from the Yangtze River to Yellow River occurred at 0.8 Ma. Large-scale transgression in the Yellow Sea began at 0.8 Ma, possibly related to subsidence of the Min-Zhe Uplift. Tectonic deformation, rather than climate change, is the major control on the evolution of the Yellow and Yangtze Rivers.